NEUROANATOMIA E COMUNICAÇÃO - Daniella Cavalcante Antunes; Kátia Eliane Santos Avelar; Reis Friede (TRF2, 2019)
The nervous system controls the organic functions and integration to the environment. Or it not only controls and coordinates the functions of all systems of the organism, but also, when receiving the necessary stimuli, is able to interpret themand to trigger appropriate responses to them. This article aims to explain how oral and written communication takes place neurologically, as well as its changes in the face of stroke and also the consequences that such changes can affect the life of the patient.